From hazard identification to risk assessment: The role of the prevention technician in the carcinogenic risk assessment for formaldehyde - Pattavina, Fabio; Wachocka, Malgorzata; Tuti, Federica; Boninti, Federica; Santi, Riccardo; Grossi, Roberta; Laurenti, Patrizia (Frontiers in Public Health, 2023)
The Prevention Technician in the Environment and Workplaces (PTEW) is a health professional who works in the identification, assessment, and management of risk in living and working places. The PTEW implements specific corrective actions at reducing exposure levels to chemicals such as formaldehyde. The aim of this report was to update the formaldehyde risk assessment document (RAD). The risk assessment process was divided into three steps as follows: (1) preliminary data collection, (2) an on-site visit to identify the use patterns and process, and (3) application of the algorithm to calculate the exposure levels of healthcare workers. In addition, with the introduction of closed-circuit systems, 23 devices were evaluated to identify possible airborne dispersion of formaldehyde. The algorithm was applied in 31 hospital units and the results allowed us to classify the staff in two levels of exposure for each hospital unit; healthcare workers were classified as “exposed” or “potentially exposed.” Most of the HCWs are categorized as potentially exposed, and only workers working in laboratories are considered to be exposed. The results showed that devices must be used properly according to the user manual. To increase the level of worker safety, we have proposed to introduce closed-circuit safe handling systems and keeping the duration and intensity of exposure at the lowest possible levels according to the “ALARA” principle. The assignment of the Italian PTEW is to achieve excellence in the levels of health and safety of patients and hospital workers by pursuing a shared mission: improving the quality of public health.